PENERAPAN METODE SNOWBALL THROWING DALAM MENINGKATKAN KETERAMPILAN MAHARAH KALAM SISWA MADRASAH ALIYAH - Asni Furoidah; Umi Badriatus Sholihah (As-Sulthan Journal of Education, 2026)
This research aims to improve students' speaking skills (maharah kalam) through the application of the snowball throwing method at Madrasah Aliyah Raudlatut Tholabah Paleran, Jember. The low activity of students and limited confidence in communicating using Arabic are the main background of this study. The research method used is Class Action Research (PTK) which is carried out in two cycles. Each cycle consists of planning, implementation, observation and reflection stages. The subject of the study was 27 students in grade XI of Madrasah Aliyah. Data collection was carried out through observation of learning activities, interviews and oral tests to measure students' ability to understand the language. The results of the study show that the application of the snowball throwing method can significantly improve the skills of maharah kalam. Students become more active, responsive and confident in expressing ideas spontaneously using Arabic. This increase is evidenced by the increase in the average grade of the class from the pre-cycle stage to cycle II which achieves the set success indicators. Thus, the snowball throwing method is effectively used as a collaborative learning strategy that is fun and challenging for students at the Madrasah Aliyah level.